Public Complaint Application (Case Study of RSUDYA Tapaktuan Based On Android) - Fardiansyah; Sera Delta Tanjung; Sri Mulia Rezeki (Jurnal Inotera, 2020)
Yuliddin Away Regional General Hospital (RSUDYA) as an institution provides individual health services in a complete manner that often experiences obstacles in providing optimum services to community, in some cases, complaints from the public. During this time, complaints are accommodated by the existence of a complaint box in each service division, but the use of this method is difficult to obtain accurate information and the process of executing these complaints requires a relatively long period. The implementation of information and communication technology in the form of applications is expected to improve responsive and informative service quality. Through the Android-based Complaints application, it was found that with the use of this application the community was easy in providing advice and criticism of the services of Yuliddin Away Hospital.